Motivations and logics of adherence of Moroccan companies to CSR strategies - El Hammoumi , Zineb; Nafzaoui, Mohamed Achraf (Revue Internationale du Chercheur, 2023)
The tensions currently weighing on the world continue to support the legitimacy of resorting to a transversal economic model like sustainable development. Some companies rally behind this cause and apply the principles of sustainable development in their strategy, through the concept of CSR. However, the reasons for this commitment are numerous and sometimes even contradictory. This article aims to feed the reflections around the strategic motivations and the logics of adhesion which explain the adoption of the CSR strategies by the companies in Morocco. Our construction is based on modeling by structural equations in order to explain the factors related to this commitment.